Soil impacts caused by coal mining and coal mine waste (Revista de Ciências Agroveterinárias, 2010)
The Coal basin of Santa Catarina is located between the towns of Araranguá and Lauro Müller and contains a reserve of mineral coal around 4.3 billion tons, corresponding to 13% of the country total exploitation. Coal mining is done in underground and in surface mines, and both processes lead to environmental problems. Until the late 1990’s, the reject was, in most cases, deposited in open areas close to mining sites or coal beneficiation. Thus, an area of approximately 6,400 hectares was degraded. In January 2000, the Department of Public Prosecution ordered the Union and the Union of Mining Industries to adopt safer rules for the reconstruction of areas still being mined, and to recover areas previously degraded by the activity. The recovery of such areas undergoes primarily the knowledge of key issues that may prevent restoration of ecological functions of impacted soils; these functions depend directly on physical and chemical soil properties. The chemical and physical properties of soils built post-coal mining reflect the inherited variability of geological materials, different construction processes, thickness and degree of layers compaction, degree of material mixing of the geologic column, mixing degree of reject and soil and presence or absence of acid mine drainage. The interaction of these factors results in the complexity and diversity of problems found when attempting to recover the degraded areas of mining coal in Santa Catarina State, Brazil.
Keywords: Recovery of degraded area; Coal mining; Acid mine drainage.